Model reference adaptive control and LQR control for quadrotor with parametric uncertainties - Abdul Ghaffar, Alia Farhana; Richardson, Tom (World Academy of Science, Engineering and Technology, 2015)
A model reference adaptive control and a fixed gain LQR control were implemented in the height controller of a quadrotor that has parametric uncertainties due to the act of picking up an object of unknown dimension and mass. It is shown that an adaptive controller, unlike the fixed gain controller, is capable of ensuring a stable tracking performance under such condition, although adaptive control suffers from several limitation. The combination of both adaptive and fixed gain control in the controller architecture can result in an enhanced tracking performance in the presence of parametric uncertainties.